Pengaruh Price Earning Rasio (PER) dan Price To Book Value (PBV) Terhadap Volume Perdagangan Saham Perusahaan Sub Sektor Makanan dan Minuman di BEI - Ketnita Marampa; Agustinus Mantong; Jens Batara Marewa (CV. Ulil Albab Corp, 2024)
The purpose of this study intends to see the effect of price earning ratio and price to book value on stock trading volume in food and beverage sub-sector companies on the Indonesia Stock Exchange using multiple linear regression analysis. Sample selection in this study used purposive sampling method. The sample in this study is a food and beverage sub-sector company that uses rupiah currency units in financial statements published on the Indonesia Stock Exchange in 2018-2022 with a sample of 7 issuers from 15 issuers and uses a statistical program application, namely SPSS 26. The calculation results with the t test on the variable price earning ratio < with values (-0.430) < (2.037) and on the variable price to book value > with values (2.308) > (2.037). The conclusion of this study is that the price earning ratio and price book value do not simultaneously affect the stock trading volume of food and beverage sub-sector companies on the Indonesia Stock Exchange. However, only the price to book value variable has a significant partial positive effect on the stock trading volume of food and beverage sub-sector companies on the IDX The results of this study can be used as a practical analysis tool for investors in stock trading